Techno-Economic and Socio-Environmental Study of a Floating Photovoltaic Project on Lake Yojoa , Cortés, Honduras (LACCEI, 2024)
Honduras is a country that is undergoing a transition to renewable energies, steering away from fossil fuels. However, the electricity loss in the transmission and distribution lines has slowed down this transition. The exponential increase in the electricity tariff due to the accretion of fossil fuel cost, and the restrictions imposed during 2020 due to the COVID-19 pandemic have affected economically the small and medium restaurants in the touristic zone in Lake Yojoa, Honduras. The implementation of a floating photovoltaic microgrid-type system can diminish the economic impact endured by the restaurants by implementing a new monomial tariff for electricity, and attract more tourist to the area, activating the economy and promoting the transition to renewable energies at the same time. In this study, the feasibility of the technical, economic, social, and environmental aspects of the project were evaluated utilizing real measurements obtained from a reference restaurant and utilized for all the 67 restaurants in the area. In the economic aspect, a new monomial tariff was obtained, utilizing the national grid’s electricity tariff and the floating photovoltaic project’s electricity tariff, and furthermore the values of the levelized cost of electricity (LCOE), internal rate of return (IRR), return on investment (ROI), and recovery period of the project for both scenarios: with and without financing, being the financed scenario superior to the other. Environmentally the results obtained showed a decrease in CO2 emissions and socially the project had an 87% acceptance rate with the restaurants. This investigation can be used by the central government as a basis for future floating photovoltaic projects that help with the decentralization of energy generation and to mitigate the electric power loss in the transmission lines.